Book review: Llegir la Imatge. Il·lustrar la Paraula. Reflexions al voltant del llibre il·lustrat i el còmic - Ana Isabel Martínez-Hernández (Universitat Jaume I. Department of English Studies, 2021)
Llegir la imatge. Il·lustrar la paraula. Reflexions al voltant del llibre il·lustrat i el còmic (Reading the image. Drawing the word. Reflections on comic books and illustrated literature, in English), edited by Julia Haba-Osca and Robert Martínez-Carrasco (2020), is a compendium of short articles written in Catalan. The book is the resulting outcome of a series of conferences, International Symposium of Innovation about Illustrated Literature, celebrated at the Universitat de València. Each of these articles acts as an individual chapter within the book, which compiles a total of fourteen of these. Speakers from different professional backgrounds and fields of knowledge related to the role of the printed image as a means of communication were invited to participate in the symposia and the subsequent compendium. This variety is reflected in the different thoughts, ideas, and views on the role of image in literature that encourage the reader to analyse and consider other perspectives. The book champions the view of illustrated literature as a graphic and visual literary genre in its own right. The book aims to open the reader's critical eye towards the use of illustrated literature to convey meaning and stimulate the reader's interpretive skills.